2015
DOI: 10.7554/elife.08483
|View full text |Cite
|
Sign up to set email alerts
|

Re-examining the role of Drosophila Sas-4 in centrosome assembly using two-colour-3D-SIM FRAP

Abstract: Centrosomes have many important functions and comprise a ‘mother’ and ‘daughter’ centriole surrounded by pericentriolar material (PCM). The mother centriole recruits and organises the PCM and templates the formation of the daughter centriole. It has been reported that several important Drosophila PCM-organising proteins are recruited to centrioles from the cytosol as part of large cytoplasmic ‘S-CAP’ complexes that contain the centriole protein Sas-4. In a previous paper (Conduit et al., 2014b) we showed that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
56
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 44 publications
(56 citation statements)
references
References 25 publications
0
56
0
Order By: Relevance
“…To test this, we estimated the amounts of Cep152, PCNT, and CDK5RAP2 recruitment to interphase centrosomes of CCB02‐treated two centrosomes‐containing MCF10A cells. Notably, both human and Drosophila CPAP interacts with these proteins to form the S‐CAP complex (Gopalakrishnan et al , ; Conduit et al , ; Chou et al , ). High‐resolution imaging and heat map intensity analyses revealed that interphase centrosomes recruit enhanced amounts of these proteins compared to vehicle‐treated cells (Fig A and B).…”
Section: Resultsmentioning
confidence: 99%
“…To test this, we estimated the amounts of Cep152, PCNT, and CDK5RAP2 recruitment to interphase centrosomes of CCB02‐treated two centrosomes‐containing MCF10A cells. Notably, both human and Drosophila CPAP interacts with these proteins to form the S‐CAP complex (Gopalakrishnan et al , ; Conduit et al , ; Chou et al , ). High‐resolution imaging and heat map intensity analyses revealed that interphase centrosomes recruit enhanced amounts of these proteins compared to vehicle‐treated cells (Fig A and B).…”
Section: Resultsmentioning
confidence: 99%
“…For quantitative approaches such as FRAP, FRET, FLIM, and FCS, the CLSM apparatus remains the workhorse, although other methods may be used instead (i.e. SIM can be combined with FRAP [Conduit et al, 2015] and STED can be used for FCS [Lanzanò et al, 2017]). With no doubt, recently developed advanced superresolution methods (such as SIM, PALM, STORM, and STED, software-based superresolution approaches, and Airyscan CLSM) and methods for long-term developmental imaging (such as LSFM and SPIM) have provided new dimensions and perspectives for better imaging of plant cells, especially in terms of significantly improved spatial and temporal resolution.…”
Section: Discussionmentioning
confidence: 99%
“…By contrast, GFP-Cnn fluorescence initially recovers in the central region of the PCM, which is significantly broader than the toroidal region where Spd2-GFP initially recovers, thereby indicating Spd2 and Cnn may not be incorporated into PCM together as part of the same complex. The same group then used two-color 3D-SIM FRAP and found that Sas4 molecules are recruited exclusively to growing daughter centrioles, whereas the PCM components Spd2 and Cnn are recruited only around mother centrioles (Conduit et al 2015). This finding contrasts that of a previous study which showed that Cnn is part of the multi-protein S-CAP (Sas4-Cnn-Asl-Dplp) complex that is pre-assembled in the cytosol before being recruited into the centrosome (Gopalakrishnan et al 2011).…”
Section: Other Techniques 3d-sim Frapmentioning
confidence: 72%